2022
DOI: 10.3389/fcimb.2022.999737
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial nucleoid-associated protein HU as an extracellular player in host-pathogen interaction

Abstract: HU protein is a member of nucleoid-associated proteins (NAPs) and is an important regulator of bacterial virulence, pathogenesis and survival. NAPs are mainly DNA structuring proteins that influence several molecular processes by binding the DNA. HU´s indispensable role in DNA-related processes in bacteria was described. HU protein is a necessary bacterial transcription factor and is considered to be a virulence determinant as well. Less is known about its direct role in host-pathogen interactions. The latest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…NAPs form numerous aggregated structures with bacterial genomic DNA and participate in processes such as replication, separation, translation, and repair of prokaryotic genomic DNA. Among the primary NAPs studied are histone‐like protein (HU), leucine-responsive regulatory protein (Lrp), virulence factor transcriptional regulator (Mga Spn ) and Histone-like nucleoid-structuring (H-NS) ( Casadesús and Low, 2006 ; Xiao et al., 2021 ; Ziegler and Freddolino, 2021 ; Ramamurthy et al., 2022 ; Stojkova and Spidlova, 2022 ).…”
Section: What Is Epigenetics?mentioning
confidence: 99%
“…NAPs form numerous aggregated structures with bacterial genomic DNA and participate in processes such as replication, separation, translation, and repair of prokaryotic genomic DNA. Among the primary NAPs studied are histone‐like protein (HU), leucine-responsive regulatory protein (Lrp), virulence factor transcriptional regulator (Mga Spn ) and Histone-like nucleoid-structuring (H-NS) ( Casadesús and Low, 2006 ; Xiao et al., 2021 ; Ziegler and Freddolino, 2021 ; Ramamurthy et al., 2022 ; Stojkova and Spidlova, 2022 ).…”
Section: What Is Epigenetics?mentioning
confidence: 99%
“…In vivo HU homologs affect gene expression and change the distribution of RNA polymerase by altering DNA topology within promoter regions or promoting long-range DNA contacts (11, 12). Recent studies have revealed that HU homologs influence transcription of genes connected to stress response or virulence in many bacterial species including: E. coli ( 13, 14 ) Salmonella enterica (15), Vibrio parahaemolyticus ( 16 ), Francisella tularensis (17) and Helicobacter pylori (18).…”
Section: Introductionmentioning
confidence: 99%
“…They are primarily DNA structuring proteins, but their functioning as transcription factors also has been shown [ 26 ]. Apart from its intracellular role, secretion of the HU protein and its extracellular role also have been studied [ 27 ]. HU protein exists as both homo- [ 28 ] and hetero-dimer [ 29 ].…”
Section: Introductionmentioning
confidence: 99%